Facile tuning of a polymeric dispersant for single-walled carbon nanotube dispersion. Issue 85 (16th September 2015) - Lee, Taeheon; Park, Jaehyun; Kim, Kyoungho; Mohanty, Aruna Kumar; Kim, Byoungjae; Han, Jong Hun; Jeon, Heung Bae; Lee, Young Sil; Paik, Hyun-jong
<x xml:space="preserve">Abstract</x> Poly((furfuryl methacrylate)-co-(2-(dimethylamino)ethyl methacrylate)) was synthesized and quaternized. Single-walled carbon nanotubes dispersed well in polar solvents using the polymeric dispersant.